Constraints to small and medium-sized enterprises development in Bangladesh: results from a cross-sectional study - Islam, Md. Shahidul; Hossain, Md. Faruk (The European Journal of Applied Economics, 2018)
Small and Medium Enterprises (SMEs) are the significant contributor tothe Bangladesh economy as they have the competency to create higheremployment, improve local technology, and create ground for the futuresustainable industrialization and corporate sectors. The aim of thisstudy is to identify major constraints faced by the SMEs in Bangladesh.A cross-sectional study was conducted in Narsingdi Municipality,Bangladesh and social survey method was applied to collect the data.Two-stage cluster sampling method was utilized to select respondents anddata were collected through face-to-face interview. Principal ComponentAnalysis (PCA) was used to determine significant constraints to SMEs.The study found that poor infrastructure and electricity supply arethe main constraints to the development of SMEs. Limited access tocredit, lack of proper business knowledge and plan, high domesticmarket competition, lack of skilled manpower and technology, andhigh cost of raw materials and equipment are the major constraintsnext to main constraint.